Chronic mould exposure as a risk factor for severe community acquired pneumonia in a patient requiring extra corporeal membrane oxygenation. (2015) - Thomas, Stephanie; Hassan, Ibrahim; Barker, Julian; Ashworth, Alan; Barnes, Anita; Fedor, Igor; Feddy, Lee; Hayes, Tim; Malagon, Ignacio; Stirling, Sarah; Szentgyorgyi, Lajos; Mutton, Ken; et al.
Abstract: A previously fit and well man developed acute respiratory failure due to environmental mould exposure from living in damp rental accommodation. Despite aggressive intensive care management he rapidly deteriorated and required respiratory and cardiac Extracorporeal Membrane Oxygenation. We hypothesize that poor domiciliary conditions may make an underestimated contribution to community respiratory disease. These conditions may present as acute and severe illness with non-typical pathogens identified.